Pemberdayaan kelompok ibu PKK Desa Batulappa dalam pembuatan KUBANANA Liptint Organik Multifungsi - Andi Sindi Cristina; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Sirwanti Sirwanti; Tri Puspita Sari; Nurdin Nurdin (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
Liptint is a Korean lip color product in the form of colored liquid (usually red, orange, and pink) that lasts long when blended on the lips. Liptint provides color gradations from bright red and pink to lighter colors, giving a fresh effect without being too much like lipstick. Liptint is a lip color similar to lipstick but tends to have a liquid texture. Currently, Liptint is more widely used by teenagers because the colors produced by Liptint tend to be more striking and bright than lipsticks in general. The partnership program for the community is more focused on providing commercialization potential by making KUBANANA Liptint Organic Multifunctional and Eco-Friendly for the partners of the Ms. PKK group in Batulappa Village. This activity was carried out in several stages, such as counseling on the benefits of Environmentally Friendly Multifunction Organic KUBANANA Liptint, training and demonstrations on the processing of Environmentally Friendly Multifunction Organic KUBANANA Liptint to partner groups, and mentoring. The results of this partnership program are that the community can process and utilize dragon fruit peel and Trigona honey as Environmentally Friendly Multifunctional Organic Liptint KUBANANA and produce differentiated products in the form of Environmentally Friendly Organic Lipbalm. The impact of this activity is to increase the economy of the PKK group through processing Environmentally Friendly Multifunction Organic KUBANANA Liptint.